"It doesn't mean I'm useless": how do young people experiencing psychosis contribute to their families and why are contributions sometimes overlooked?. Issue 1 (2nd January 2018) - Allman, Justin; Cooke, Anne; Whitfield, Becky; McCartney, Michelle
Abstract: Purpose : Psychosis is often seen as a "burden" on families and affected individuals frequently hold a negative view of themselves. This study explored the ways in which young adults who have experienced first-episode psychosis make a positive contribution within their families. Methods : Fifteen participants (seven young people with experience of psychosis and eight relatives) were interviewed separately. Their accounts were analysed using grounded theory methodology. Results : For many individuals, their experience had led to a catastrophic redefinition of their identity. However, they continued to contribute significantly both within their families and within their wider communities. The redefinition of identity sometimes appeared to create a "perceptual filter" whereby both the person themselves and family members overlooked or minimised their contribution, focusing instead on being alert to signs of psychosis or illness. Conclusions : Shame and a focus on symptoms rather than achievements and contributions can significantly limit opportunities, expectations and movement beyond an illness identity. It is important for clinicians to be aware of this and to help young people and their families to notice and value positive contribution, and so promote recovery, well-being and post-traumatic growth.